(untitled) (Kinesiology, 2023)
The main objective of the present study was to check the relationship between commonly used unilateral and bilateral countermovement jump (CMJ) performance variables (jump heights, unilateral CMJ jump/ bilateral CMJ jump height index, reactive strength index modified and bilateral deficit) and Force-velocity- Power (F-v-P) outcomes from loaded CMJs. Seventeen physical education students performed unilateral CMJ jumps, bilateral CMJ jumps and two-load (20 and 70% of the participant’s body mass) F-v-P tests. The results show that bilateral CMJ jump, unilateral CMJ jump height and the reactive strength index modified calculated from the bilateral CMJ jump are moderately correlated (r = 0.567-0.633, p<.05) to F0. No statistically significant correlations were found between F-v-P outcomes and unilateral CMJ jump height to bilateral CMJ jump index, reactive strength index modified calculated from the unilateral CMJ jump and bilateral deficit. Multiple linear stepwise regressions between F-v-P outcomes and performance variables revealed that only F0 can be statistically significantly predicted by CMJ height (R2 = 40 %). Although the unilateral and bilateral CMJ tests are less time-consuming and less fatiguing than the progressive loaded CMJ jump test, the results of our study show that the mechanical properties of the lower extremities obtained by unilateral CMJ jump and bilateral CMJ jump cannot be generalized to those measured by F-v-P profiling. Key words: unilateral, F-v-P profiling, strength, power, ballistic